Harakatul Jannah Mosque: Minang Identity and Islamic Mission in Diaspora (Rantau) - Abdul Wahid Hasyim; Yulia Kartika (Islam Realitas: Journal of Islamic and Social Studies, 2020)
This article discusses the efforts to strengthen cultural and ethnic identity the Minang people in diaspora (rantau), specifically in the context of the Harakatul Jannah mosque in Gadog, Ciawi, Bogor, West Java. In addition to being a symbol of the acculturation Minangkabau culture in the local community, this mosque preserves the social and religious institutions of Minangkabau custom in diasporic lands. This study uses a qualitative method. Data collection is done not only through literature review but also through direct observation. Analysis of collected data is based on heuristic, verification, interpretation, and historiographical techniques. This study finds that through the Harakatul Jannah mosque, the diasporic community from Minangkabau is able to relive the Minang tradition in social activities, education, as well as architecture. Combining European and Middle Eastern styles with traditional styles, this mosque was constructed without losing Minangkabau cultural characteristics, which are reflected in several elements, such as the Bundo Kanduang Gate, the Hajjah Tower, and the Majlis of Shaykh Ahmad Khatib al-Minangkabawi. These are manifestations of archipelago culture in architecture. In the field of education, the activities of the students and the community of the mosque shows many similarities with the Islamic intellectual tradition of 19th century Minangkabau. All educational and religious activities in the mosque aim at preserving and strengthening the Minang cultural identity in diasporic lands.Artikel ini membahas tentang penguatan identitas budaya dan kesukuan orang Minang di tanah rantau melalui Masjid Harakatul Jannah di Gadog, Ciawi, Bogor. Selain menjadi simbol akulturasi budaya Minangkabau, masjid ini menjadi jejak pranata sosial keagamaan pamangku adat Minangkabau di ranah rantau. Penelitian ini menggunakan metode kualitatif. Pengumpulan data dilakukan selain melalui kajian kepustakaan juga observasi langsung. Berdasarkan penelitian yang dilakukan ditemukan bahwa melalui masjid Masjid Harakatul Jannah, para perantau dari Minangkabau menghidupkan tradisi Minang baik dalam aktivitas sosial, pendidikan, dan keagaman maupun arsitektur bangunan. Manifestasi arsitektur itu di antaranya menggabungkan gaya Eropa dan Timur Tengah dengan gaya tradisional pada bangunan mesjid. Hal ini  tercermin dalam beberapa elemen masjid, seperti pintu Bundo Kanduang,  Tower haji, dan  Majlis Shaykh Ahmad Khatib al-Minangkabawi. Sementara itu dalam bidang pendidikan, aktivitas model surau yang dimodifikasi menunjukkan kemiripan dengan tradisi intelektual Islam di Minangkabau abad ke-19. Dengan demikian, arsitek bangunan dan aktivitas keagamaan di masjid tersebut merupakan bentuk penguatan identitas budaya Minang di tanah rantau.